2017
DOI: 10.3892/ijo.2017.4234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cell-cell crosstalk on gene expression patterns in a cell model of renal cell carcinoma lung metastasis

Abstract: The median survival rate of patients with metastatic renal carcinoma is approximately 10 to 12 months, with up to 50% of patients developing metastases in the lung parenchyma. The molecular basis for metastatic development remains unclear. In the present study, we used renal cell carcinoma (RCC) cells and bronchial epithelial cells, representing metastasis target organ cells, conditioned medium and co-culture models to identify specific gene expression changes responsible for cancer cell viability in a metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Whole genome studies, microarray or next generation sequencing analysis, as well as fluorescent and bioluminescent imaging, may reveal how RCC subtypes differ not only in primary tumor characteristics but also in their metastatic behavior, in particular lung- or abdomen-homing characteristics or bone-seeking phenotype. Understanding the physiological link between the deregulation of specific genes and homing of certain metastases may impact treatment of RCC patients in the future 17,43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole genome studies, microarray or next generation sequencing analysis, as well as fluorescent and bioluminescent imaging, may reveal how RCC subtypes differ not only in primary tumor characteristics but also in their metastatic behavior, in particular lung- or abdomen-homing characteristics or bone-seeking phenotype. Understanding the physiological link between the deregulation of specific genes and homing of certain metastases may impact treatment of RCC patients in the future 17,43 .…”
Section: Discussionmentioning
confidence: 99%
“…In the current state of knowledge, clinicians still lack the ability to predict to which category each patient will belong (fast, slow, or medium-progressors) but for long time it has been suggested that general tumor and metastatic burden might be one of the factors influencing the outcome 1113 . Despite many advances in understanding RCC biology 1417 , there is still a great deal of information to be discovered regarding the behavior of mRCC treated with VEGF-inhibiting agents both in molecular and clinical analyses 18,19 . Overall, measuring the size of tumors remains the simplest way to estimate the severity of disease and possibly predict response/progression on treatment in routine clinical practice world-wide.…”
Section: Introductionmentioning
confidence: 99%
“…The cell–cell crosstalk is an indirect cell–cell communication and plays an important role in biological systems. For instance, cell–cell crosstalk can influence gene expression patterns [ 35 ], and involve in the development and regeneration of the respiratory system as well [ 36 ]. For each cell–cell pair, a higher similarity means sharing more number of miRNA-mRNA interactions or hub miRNAs between two cells.…”
Section: Methodsmentioning
confidence: 99%
“…The cell-cell crosstalk is an indirect cell-cell communication and plays an important role in biological systems. For instance, cell-cell crosstalk can influence gene expression patterns [33], and involve in the development and regeneration of the respiratory system as well [34]. For each cell-cell pair, a higher similarity means sharing more number of miRNA-mRNA interactions or hub miRNAs between two cells.…”
Section: Methodsmentioning
confidence: 99%